TINJAUAN YURIDIS PENANGKAPAN IKAN TANPA SIPI DAN MENGGUNAKAN JARING TRAWL - Ernawaty Putri Elisabet Siburian; Dyah Setyorini (Fakultas Hukum Universitas Trisakti, 2022)
Every fishing activity in the water area of ​​the Republic of Indonesia must have a permit and meet the requirements for the use of fishing nets as regulated in the Regulations. This research discusses Fishing without SIPI. This research is normative and descriptive analytical legal research, using secondary data obtained through library research. The data is analyzed qualitatively and the conclusions are drawn using deductive logic. The conclusion from this research is the fishing by Sugianto did not use SIPI and violated article 27 paragraph (1) Law Number 45/2009 from Law Number 31/2004 concerning fishery and Sugianto also using nets in the form of Trawls Nets. On the other hand the actions he did categorized as Illegal Fishing.